Updates for publishers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
As from January 2003, the email address for Hans Zell Publishing, the source of the African Publishing Companion, is hanszell@hanszell.co.uk.The Website is unchanged atwww. hanszell.co.uk.The Bellagio Publishing Network has launched an open...